John Love correspondence - Love, John, active 1847.
ALS (1847 February 4; Monterey, Mexico) pertaining to the Mexican War and mentioning Winfield Scott and Zachary Taylor. Addressed to Lieut. Jno. Love; written by a U.S. Army officer, signed L. G.
U.S. Army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Scott, Winfield, -- 1786-1866.; Taylor, Zachary, -- 1784-1850.; United States. -- Army -- History -- Mexican War, 1846-1848.; Mexican War, 1846-1848 -- Personal narratives; Monterrey (Mexico) -- History; Army officers